Internal and External Forces Measurement of Planar 3-DOF Redundantly Actuated Parallel Mechanism by Axial Force Sensors. (9th October 2013) - Harada, Takashi; Liu, Podi
Abstract : This paper proposes a method for measuring the internal and external forces of a planar 3-DOF (degree of freedom) redundantly actuated parallel mechanism. The internal forces, force acts inside the endplate and mechanism constraint force, and the external forces, forces act on the endplate and thrusts by actuators, were measured simultaneously using the axial forces of the rods. Kinetostatic equations of the parallel mechanism were used to derive algorithms for measuring the internal and external forces. A link axis force sensor was developed using a strain gauge sensor. To verify the actual internal force of the endplate, a force sensor was also installed on the endplate. A real-time system for measuring the forces of the parallel mechanism was developed using RT-Linux. The external and internal forces were measured accurately.